Design and characterization of a heterobifunctional degrader of KEAP1 - Hao Chen; Nghi H. Nguyen; Charlene M. Magtoto; Simon A. Cobbold; Grace M. Bidgood; Lizeth G. Meza Guzman; Lachlan W. Richardson; Jason Corbin; Amanda E. Au; Bernhard C. Lechtenberg; Rebecca Feltham; Kate D. Sutherland; et al. (Redox Biology, 2023)
The Kelch-like ECH-associated protein 1 (KEAP1) - nuclear factor erythroid 2-related factor 2 (NRF2) signaling pathway senses reactive oxygen species and regulates cellular oxidative stress. Inhibiting KEAP1 to activate the NRF2 antioxidant response has been proposed as a promising strategy to treat chronic diseases caused by oxidative stress. Here, we developed a proteolysis targeting chimera (PROTAC) that depletes KEAP1 from cells through the ubiquitin-proteasome pathway. A previously developed KEAP1 inhibitor and thalidomide were incorporated in the heterobifunctional design of the PROTAC as ligands for KEAP1 and CRBN recruitment, respectively. Optimization of the chemical composition and linker length resulted in PROTAC 14 which exhibited potent KEAP1 degradation with low nanomolar DC50 in HEK293T (11 nM) and BEAS-2B (<1 nM) cell lines. Furthermore, PROTAC 14 increased the expression of NRF2 regulated antioxidant proteins and prevented cell death induced by reactive oxygen species. Together, these results established a blueprint for further development of KEAP1-targeted heterobifunctional degraders and will facilitate the study of the biological consequences of KEAP1 removal from cells. This approach represents an alternative therapeutic strategy to existing treatments for diseases caused by oxidative stress.